Status-seeking policies of middle powers in status clubs: the case of Turkey in the G20 - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This study applies the theoretical framework of Social Identity Theory (SIT) and its three main strategies, social mobility, social competition and social creativity to Turkey as an emerging middle power in the G20. In doing so, it uses Role Theory's toolkit in order to assess the impact of Turkey's middle power role conception, role expectations, and role performance on identity management strategies pursued by Turkey vis-a-vis its middle power peers in the G20 (namely Canada, Australia, Korea, Brazil, Mexico, and South Africa). The findings of this study acknowledge that Turkey's status-seeking policies as an emerging middle power are more prone to pursuing social mobility and social creativity rather than social competition. It concludes that Turkey's weakness in enacting its G20 middle power role and its failure in bridging this middle power role to its middle power status in turns it to an underperforming middle ranked country in the G20.
Keywords: Social Identity Theory (SIT); Role Theory; status politics; middle powers; G20; Turkey